Reward System Analysis on Employee Performance Improvement - Dewi Andriani (Eduvest - Journal of Universal Studies, 2022)
This research is motivated by the phenomenon of giving rewards that are not evenly distributed. The purpose of this study is to analyze the importance of the reward system in improving employee performance. This research uses a qualitative method with a literature review approach. The results of this study indicate that one form of reward is the provision of incentives. Incentives will enhance employee motivation in an effort to achieve the goal of improving performance. Motivation is an indicator that affects performance because it is an important driver that causes people to work is the need that must be met. Thus, through a reward system in the form of incentives, it can generate employee work motivation, where motivation is the main factor in improving employee performance so as to increase employee productivity and welfare.